From co-regulation to self-regulation: maternal soothing strategies and self-efficacy in relation to maternal reports of infant regulation at 3 and 7 months - Kiel, Natalie; Şamdan, Gizem; Wienke, Annika S.; Reinelt, Tilman; Pauen, Sabina; Mathes, Birgit; Herzmann, Charlotte (Infant mental health journal, 2024)
This study, conducted in Germany, examines the role of maternal soothing strategies to explain the association of maternal self-efficacy with infant regulation (crying and sleeping behavior). Questionnaire data of 150 mothers, living in Germany, with mixed ethnic and educational backgrounds were collected when infants were 3 and 7 months old. Two types of maternal soothing strategies were distinguished: close soothing, involving close physical and emotional contact, and distant soothing, involving physical and emotional distancing from the infant. A cross-sectional SEM at 3 months indicated that maternal self-efficacy is associated with reported infant regulation through distant soothing strategies. Low maternal self-efficacy was associated with frequent maternal use of distant soothing, which in turn was related to reported infant regulation problems, that is, non-soothability and greater crying frequency. Frequent use of close soothing was associated with reported infant sleeping behavior, that is, frequent night-time awakenings. A longitudinal SEM further indicated that the effects of close soothing persisted at least until the infants' age of 7 months. The study showed how low maternal self-efficacy, increased use of distant soothing, and reported early infant regulation problems are intertwined and that, due to their persisting positive effect on infant soothability, close soothing better supports infant development.
Zuerst veröffentlicht: 4. Januar 2024
Gesehen am 25.07.2024